The Merrifield-Simmons index for two types of phenylenes - Seibert, Jaroslav; Koudela, Libor (Slovenská technická univezita v Bratislave, 2020)
The Merrifield-Simmons index i(G) of a simple undirected graph G=(V,E) is the number of all independent sets of vertices in G. This number is one of the most popular topological indices in chemistry. In this contribution we obtain exact formulas for the Merrifield-Simmons index of two types of the branched phenylenes whose molecular graph consists of two linear chains of alternating hexagons and quadrangles, together forming a bent chain.
Merrifield-Simmons index dvou typů phenylenů
Keywords: difference equation; bent phenylene; Merrifield-Simmons index; diferenční rovnice; lomený phenylene; Merrifield-Simmonsův index